BRII (Building the Research Information Infrastructure) Project: Final Report - Rumsey, S; Loureiro-Koechlin, C; Bowtell, A (2010)
The aim of the project is to enable efficient sharing of research management data (ie data about research at the University of Oxford) from a selection of existing data stores and to create exemplar services that disseminate and re-use that data using a lightweight solution based on semantic web technologies. FINDINGS: The stakeholder analysis revealed the practice and motivations of users who were categorised into three broad groups: individual researchers; administrators; disseminators and strategists. Generally users were in favour of the basic premise of the registry. Over the period of the project, conflicting attitudes towards data aggregation, dissemination and re-use became clear. Data sources were categorised with respect to their ease of harvesting and synchronising for the registry. A variety of types of data stores emerged – some were easy to harvest whilst others presented considerable problems for synchronising. ACHIEVEMENTS: The registry contains a good quantity of data from a number of different sources. The technical design of the registry has generated considerable interest within the developer and research information communities. There have been additional outputs to those predicted including the vocab.ox.ac.uk site for vocabularies. The stakeholder analysis provides valuable insight into stakeholder motivations and practice. The Blue Pages interface is easy to use and test users like the service. CONCLUSIONS: Overall the project has been successful but not without problems. It met all its aims and objectives and generated much interest both internally and externally. Additional software outputs were created and released. The original intention was to make the Blue Pages freely available: consultation and feedback resulted in the resource remaining limited to within the Oxford only domain. The work of the project has been presented to high level committees of the University and a final decision regarding its future adoption as a central service has not yet been reached. The Medical Sciences Division ‘themed’ website (under construction) and the Blue Pages provide valuable examples of use of registry data.